Eco‐Friendly Needleless Electrospinning and Tannic Acid Functionalization of Polyurethane Nanofibers with Tunable Wettability and Mechanical Performances. Issue 6 (28th January 2022) - Dodero, Andrea; Castellano, Maila; Vicini, Silvia; Hébraud, Anne; Lobry, Emeline; Nhut, Jean‐Mario; Schlatter, Guy
Abstract: Electrospinning is the leading process allowing the fabrication of polymeric nanofibrous membranes and mats. Unfortunately, it generally requires the solubilization of the polymer in a toxic solvent causing health and environmental issues during the production. Here, it is demonstrated that polyurethane (PU) fibrous membranes can be produced by electrospinning and then, moreover, functionalized using water as the only solvent for each processing step. Waterborne polyurethane in the form of a dispersion is firstly electrospun using poly(ethylene oxide) (PEO) as template polymer. After removing PEO via a washing cycle in water, the membranes show physico‐chemical properties influenced by the initial polymeric component ratio with greater mechanical performances and hydrophobicity observed at a higher PU amount. Aqueous solutions of bio‐based tannic acid (TA) are then employed to modify the surface properties of the membranes. The high amount of galloyl units per TA molecule allows its efficient anchoring on the fiber surface through supramolecular hydrogen bonding. By varying the TA amount and the order of washing cycle, the wettability can be tuned expanding the application range of the membranes. Finally, their efficient electrospinning at high flow‐rate using a home‐made needleless emitter paves the way for industrial production via full environmentally green processing. Abstract : Nanofibrous membranes with tunable wettability and mechanical properties are prepared via full environmentally friendly approach using green electrospinning of waterborne polyurethane. The fiber surface has been subsequently functionalized in water thanks to supramolecular hydrogen bonding with tannic acid. Efficient electrospinning at high flow‐rate using a home‐made needleless emitter paves the way for industrial production.